Charcot neuro-osteoarthropathy: a review of key concepts and an evidence-based surgical management algorithm - Argyropoulos, Miltiadis; Wynell-Mayow, William; Johnson, Oscar; Faroug, Radwane; Johal, Karanjeev Singh; Deol, Rupinderbir Singh; Hakmi, Atef; Mordecai, Simon (Frontiers in Clinical Diabetes and Healthcare, 2024)
Charcot neuro-osteoarthropathy (CNO), mainly as a result of diabetic neuropathy, is a complex problem which carries significant morbidity, and is an increasing burden on healthcare as demographics change globally. A multi-disciplinary team (MDT) is necessary to treat the multiple facets of this disease. The multifactorial and non-homogenous nature of this condition and its management, has prevented the development of comprehensive guidelines based on level 1 evidence. Although there is a trend to surgically treat these patients in tertiary centres, the increasing prevalence of CNO necessitates the capability of all units to manage this condition to an extent locally. This article conducted a thorough literature search of Pubmed and Embase from 2003 to 2023 including the following search terms; “Charcot” “neuroarthropathy” “diabetic foot” “management” “surgery” “treatment” “reconstruction”. The results of this review have been summarised and synthesised into an evidence-based algorithm to aid in the surgical decision-making process, and improve the understanding of surgical management by the whole MDT.